2009
DOI: 10.1111/j.1744-7348.2009.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow rows reduce biomass and seed production of weeds and increase maize yield

Abstract: Smallholder farmers in southern African countries rely primarily on cultural control and hoe weeding to combat weeds, but often times, they are unable to keep up with the weeding requirements of the crop because of its laboriousness, causing them to incur major yield losses. Optimisation of crop planting pattern could help to increase yield and suppress weeds and to reduce the critical period of weed control and the weeding requirements to attain maximum yield. Experiments were carried out in Zimbabwe during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…It is possible that excessive shading may have resulted in clover death. Weed scientists have used crop shading as a fundamental tenant of weed control, emphasizing a need for weed control between rows of a crop until the time of canopy closure (Teasdale, 1995;Mashingaidze et al, 2009;Marín and Weiner, 2014). Therefore, the impact of shading by the corn crop on the clover was determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that excessive shading may have resulted in clover death. Weed scientists have used crop shading as a fundamental tenant of weed control, emphasizing a need for weed control between rows of a crop until the time of canopy closure (Teasdale, 1995;Mashingaidze et al, 2009;Marín and Weiner, 2014). Therefore, the impact of shading by the corn crop on the clover was determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that uniform planting pattern increases the spatial uniformity in leaf area index (LAI), reduces mutual shading, and hastens canopy closure, all of which result in increased radiation interception (RI) by the canopy (Olsen & Weiner, 2007) and increased crop growth and yield (Mashingaidze et al, 2009). At the same time, an equidistant spacing of crop plants may reduce light penetration or affect light quality (or both) under the crop canopy.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, an equidistant spacing of crop plants may reduce light penetration or affect light quality (or both) under the crop canopy. This may restrict seed germination of some weed species, suppress weed seedling growth, and reduce seed production by weed plants (Mashingaidze et al, 2009). In a uniform pattern, intra-specific competition within the crop is delayed, while inter-specific competition with weeds begins sooner.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of resources (water, nutrients, and space) and environmental factors like light and temperature affect the extent of the competition in weed-crop settings (Guillemin et al 2013). Studies with a number of crops like wheat (Kristensen et al 2008, Mashingaidze et al 2009), rice (Chauhan & Johnson 2010, barley (Kolb et al 2010), cotton (Reddy 2001), millet (Shinggu et al 2009), sorghum (Grichar et al 2004, and soybean (Hock et al 2006) found inverse relationships between narrow crop rows and weed growth.…”
Section: Discussionmentioning
confidence: 99%
“…It was earlier suggested by Holt (1995) that by manipulating the crop row spacing and orientation in row cultivation, there may be reduction in light interception by weeds. Crop shading via narrow row spacing can improve weed control without extra costs or negative environmental impacts (Barberi 2002) whereby narrow rows provide a competitive edge to the crop over weeds due to early and rapid canopy closure (Kristensen et al 2008, Mashingaidze et al 2009, Chauhan & Johnson 2010, Khaliq et al 2014). Significant differences (p≤0.05) were recorded in the dry weed biomass for both seasons among the treatment combinations.…”
Section: Discussionmentioning
confidence: 99%